Gene-occupation interactions: a review of the literature on bladder and prostate cancer - Edyta Wieczorek; Anna Wolniakowska; Joanna Roszak; Robim M. Rodrigues; Tamara Vanhaecke; Edyta Reszka (Nofer Institute of Occupational Medicine, 2023)
Bladder cancer (BCa) and prostate cancer (PCa) are genitourinary cancers which constitute significant health problems in men and in which environmental factors play an important role. Understanding the genetic susceptibility to BCa or PCa and occupational exposure is paramount to improving cancer prevention and early detection. The aim of this review article was to address the scientific evidence on the genetic risk factors and occupational exposure associated with the occurrence of BCa and PCa. The authors identified relevant original articles that have been published between 1994 and 2023. Variations of the following search terms: "gene" and "occupational" combined with one of the following terms: "bladder cancer" or "prostate cancer" were applied for the search purpose. The authors found 342 publications of which 50 population studies met their requirements for gene-occupation interactions. In total, 34 full-text manuscripts were about BCa and 16 about PCa. These research examines the genes involved in detoxification processes of xenobiotics (glutathione S-transferase, N-acetyltransferase, cytochrome P450, UDP-glucuronosyltransferase), oxidative stress (glutathione peroxidase 1, manganese superoxide dismutase, catalase), altering DNA repair capacity (X-ray repair cross-complementing 1, base excision repair, nucleotide excision repair), tumour suppression ( TP53 gene), and vitamin D pathway (vitamin D receptor gene). The role of genetic factors in the occupational exposure has not been conclusively established, but it appears the possibility of genetic involvement. Determination of environmentally responsive genes provides important mechanistic implications for the etiology of occupational cancers, and valuable input in occupational exposure limits set by taking genetic susceptibility into account. More genetic research is needed to corroborate these findings and assess their significance in the workplace. Med Pr. 2023;74(2):127-44